PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN ANIMASI SPARKOL VIDEOSCRIBE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PRODUKTIF KELAS XI MULTIMEDIA DI SMKN 3 BONE - Nurannisa; Abd. Haling; Pattaufi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The objectives of this thesis are (1) To find out an overview of the use of Sparkol Videoscribe animated learning media in productive subjects (2) To find out a picture of student learning outcomes taught using Sparkol Videoscribe animated learning media (3) To find out the effect of using Sparkol animated learning media videoscribe on student learning outcomes. This research was conducted using a quantitative approach. This type of research is pre-experimental design. The population in this thesis is all students in class XI Multimedia at SMK Negeri 3 Bone, totaling 30 students, consisting of 5 male students and 25 female students. Because the population of this study is relatively small and can be reached, the researcher decided to use a saturated sampling technique. Data collection techniques used observation, test and documentation techniques in this research. The results of data analysis consist of the results of teacher implementation activity data analysis and the results of student activity data analysis. The test consists of a pretest given before being given treatment using the Sparkol Videoscribe animation learning media and a posttest after being given treatment using the Sparkol Videoscribe animation learning media. Data analysis uses descriptive statistical analysis and inferential statistical analysis. The results of this research show: Student learning outcomes in productive subjects before using learning media (pretest) with an average score of 55% and after using learning videos (posttest) are relatively high with an average score of 81.3% of learning outcomes in Class XI Multimedia students' productive subjects are increasing. There is a positive and significant influence of the use of Sparkol Videoscribe animation learning media on student learning outcomes in productive class XI multimedia subjects at SMKN 3 BONE, it is stated to be accepted.